Un modele de gauchissement des coques - Hassis, Hedi (European Journal of Computational Mechanics, 1999)
The warping high-order theory of plate deformation developed in [HAS 98] is extended here to shells. A theory of shell deformation is derived which accounts for the effects of transverse shear deformation and a non linear distribution of the insurface displacements with respect to the thickness coordinate. This theory uses the normal modes associated to the normal fibre (considered such as a geometrical beam) as basis functions. Using only the rigid body modes, we find the classical theory and using the deformation normal modes, a high order theory is constructed. Our theory is compared with other theory and the exact solution through application to a particular problem of shells.